ADAPTIVE FISCAL POLICY: BALANCING ECONOMIC STIMULUS AND BUDGET SUSTAINABILITY - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research discusses adaptive fiscal policy patterns and strategies in balancing the need for economic stimulus with the principle of budget sustainability in Indonesia. Through the literature review method, this research analyses the government's response to the economic crisis, particularly during the COVID-19 pandemic and other global challenges. The results show that adaptive fiscal policies, such as accelerated state spending, tax reforms, and financing innovations, are able to maintain economic stability, protect vulnerable groups, and encourage the recovery of strategic sectors. However, the effectiveness of short-term stimulus must be balanced with fiscal consolidation, deficit control, and strengthening the state revenue base to maintain fiscal sustainability. This study recommends the need for cross-sectoral synergies, periodic evaluations, and the development of innovative fiscal instruments to ensure that fiscal policy is not only responsive to the crisis, but also becomes the foundation of inclusive and sustainable economic transformation in the future.